2018
DOI: 10.1038/s41419-018-0599-5
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine kinase 1-associated autophagy differs between neurons and astrocytes

Abstract: Autophagy is a degradative pathway for removing aggregated proteins, damaged organelles, and parasites. Evidence indicates that autophagic pathways differ between cell types. In neurons, autophagy plays a homeostatic role, compared to a survival mechanism employed by starving non-neuronal cells. We investigated if sphingosine kinase 1 (SK1)-associated autophagy differs between two symbiotic brain cell types—neurons and astrocytes. SK1 synthesizes sphingosine-1-phosphate, which regulates autophagy in non-neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 77 publications
1
35
0
Order By: Relevance
“…Since neurons are highly specialized post-mitotic cells, we speculated that neuronal G4 pathways may be drastically different from G4-based mechanisms in their dividing symbiotic cells, namely in astrocytes. We first confirmed that our astrocytic cultures [38] are pure astrocytes. Astrocytes were grown in culture in DMEM + serum for 3 weeks, fixed, and stained with fluorescent phalloidin and antibodies against GFAP ( Fig.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…Since neurons are highly specialized post-mitotic cells, we speculated that neuronal G4 pathways may be drastically different from G4-based mechanisms in their dividing symbiotic cells, namely in astrocytes. We first confirmed that our astrocytic cultures [38] are pure astrocytes. Astrocytes were grown in culture in DMEM + serum for 3 weeks, fixed, and stained with fluorescent phalloidin and antibodies against GFAP ( Fig.…”
supporting
confidence: 70%
“…2C and 2D). As astrocytes basally have low levels of autophagy [38,40], G4 stabilization still leads to downregulating ATG7 levels in these cells. We also looked at the levels of SQSTM1, which is commonly used as an autophagic reporter.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, little is known on the possible role of macroautophagy in the immune function of astrocytes. Recent works show that this process is needed for the homeostasis maintenance upon stimulation, but depending on the type of stressor, it can also facilitate cell death and therefore brain inflammation [128][129][130] (Figure 2).…”
Section: Cma In the Adaptive Immune Responsementioning
confidence: 99%
“…Furthermore, increased levels of S1P in neurons have a neuroprotective function via the induction of autophagy by benzoxazine. This neuroprotective role was neuron specific, since benzoxazine did not induce autophagy in astrocytes [188].…”
Section: Alteration In Sp1 and Cer In Neurodegenerative Diseasementioning
confidence: 91%